Transition Research on Problems of Handicapped Youth [Project TROPHY]. Occasional Papers Number 2 - Washington Univ., Seattle; Washington Univ., Seattle ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
These five papers deal with topics related to problems associated with transition from school to independent living for handicapped youth. "Individual Transition Plans: From Lip Service to Implementation" (Joseph Stowitschek, Cheryl Kelso) reports on a study to determine the extent to which individual transition planning is advocated by state education and vocational rehabilitation agencies and in what form. "Supported Employment: Program Features Compared to Outcomes" (Gregory Nelson, Joseph Stowitschek) describes a study to select a sample of programs high or low on selected programmatic outcomes and compare them to determine on which features they differed. "Salient Features Distinguishing Highly Active from Minimally Active Early Work Experience Programs for Mildly Handicapped Youth" (Marilyn Cohen et al.) discusses research to identify differences that exist in organizational structures and to examine distinguishing problem-solving processes that respond to obstacles presented in developing early work experiences. "The Employed Handicapped: Characteristics of Their Employers" (William Schill et al.) looks at employers who knowingly and purposefully hire handicapped individuals in terms of site size, location, and activity. "Employer Perspectives and Handicapped Employees Experiences: An Empirical Analysis" (William Schill et al.) assesses the careers of handicapped persons in the labor force. Each paper includes a bibliography. (YLB)
Sponsoring Agency: Department of Education, Washington, DC.
Contract Number: 300-85-0174.
ERIC Note: For related documents, see ED 298 280-282.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Disabilities; Education Work Relationship; Employment; Employment Level; Employment Patterns; Labor Force; Postsecondary Education; Secondary Education; Sheltered Workshops; Vocational Education; Vocational Rehabilitation; Work Experience Programs; Supported Work Programs; Information Analyses; Reports, Research